2017
DOI: 10.1002/mc.22612
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐218 inhibits tumor growth and increases chemosensitivity to CDDP treatment by targeting BCAT1 in prostate cancer

Abstract: MicroRNAs have been reported to be associated with chemosensitivity of several types of cancers. However, the underlying molecular mechanisms are poorly understood. In this study, we explored miR-218 increased the chemosensitivity to cis-diaminedichloroplatinum treatment of prostate cancer. We found that the expression level of miR-218 was down-regulated in the human prostate cancer specimens. Moreover, overexpression of miR-218 inhibited cell viability, migration, and invasion in PC3 and DU145 cells. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Notably, Xu et al have demonstrated that overexpression of BCAT1 indicates a poor survival of GC and may serve as a diagnostic and therapeutic biomarker [19]. BCAT1 usually exerts its function in regulating the tumorigenesis as a downstream target of miRNAs [34,35]. In this study, BCAT1 was determined to be a target of miR-3200-5p, which was negatively regulated by miR-3200-5p.…”
Section: Discussionmentioning
confidence: 67%
“…Notably, Xu et al have demonstrated that overexpression of BCAT1 indicates a poor survival of GC and may serve as a diagnostic and therapeutic biomarker [19]. BCAT1 usually exerts its function in regulating the tumorigenesis as a downstream target of miRNAs [34,35]. In this study, BCAT1 was determined to be a target of miR-3200-5p, which was negatively regulated by miR-3200-5p.…”
Section: Discussionmentioning
confidence: 67%
“… 29 miR-218 inhibited tumor growth and increased chemosensitivity to cisplatin in prostate cancer via negatively regulating BCAT1 protein expression. 30 In glioma cells, miR-218 affected cell proliferation, apoptosis, and invasion by negatively modulating HMGB-mediated suppression of receptor for advanced glycation end products. 31…”
Section: Discussionmentioning
confidence: 99%
“…MiR-218 involves in inhibition of GC cell growth and invasion through targeting Angiopoietin-2 [ 27 ]. Additionally, in prostate cancer, miR-218 acts as a suppressor for tumor cell proliferation [ 28 ]. For HCC, miR-218 has been validated as a down-regulated genes associated with tumor process through targeting different downstream mRNAs, such as PTEN, E2F2 [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%